PENGARUH PENDAPATAN DARI PENGGUNA KARTU JAMKESMAS TERHADAP TINGKAT PROFITABILITAS BLUD RUMAH SAKIT UMUM DAERAH SEKARWANGI CIBADAK KABUPATEN SUKABUMI PROVINSI JAWA BARAT PERIODE 2011-2013 - Hikmah, Ajeng Nurul (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This study was conducted to determine the effect of income from JAMKESMAS Card Users (X) On The Level Profitability (Y) on BLUDs Regional General Hospital Sekarwangi Sukabumi. The method used is associative method, the measurement scale used is the scale ratio of the data used secondary data. The population in this study is saturated sampling technique that the financial statements BLUDs Regional General Hospital Sekarwangi Sukabumi 2011-2013. While the sample in this research that the statements of financial position and operational reports with the number of 36 samples. Based on the results of the normality test the influence of income from card users JAMKESMAS 0,084 with significant profitability levels above 0.200 and the value of 0.005 means that the influence of income from card users JAMKESMAS normal distribution. Then from the calculation of the coefficient of determination indicates the effect of income from card users JAMKESMAS the level of profitability of 42.7% while the remaining 57.2% was obtained from other activities that are not the authors carefully in this study. From the results of simple linear regression equation is as follows : Y = a + bX Y = 0,505+ 0,663X Unknown constant value (a ) of 0.505 means Influence Revenue from card users JAMKESMAS value is zero, the level of profitability in value by 0.505 and the value of revenue Card Users JAMKESMAS ( bX ) of 0.663 which means that each increase Effect Income from card users JAMKESMAS by 1, then Profitability rate value will result in an increase of 0.663 . Furthermore, the results of the t test hypotheses Revenue Effect of Card Users JAMKESMAS to level of profitability shows that thitung> t table (5.034> 2.032245) and have a significant level of 0.000 for a significance level of less than 0.05, then this proves that H0 and H1 accepted, which means that the income of JAMKESMAS Card Users have an influence on the level of profitability. From these results expressed in the category of a close relationship , and the nature of the relationship is unidirectional , meaning the greater the revenue JAMKESMAS the greater the level of profitability.